Employment, Hours, and Earnings Consequences of Job Loss: US Evidence from the Displaced Workers Survey - Farber, Henry S. (Journal of Labor Economics, 2017)
Data are used from the 1984–2016 Displaced Workers Surveys (DWS) to investigate the incidence and consequences of job loss, 1981–2015. These data show a record high rate of job loss in the Great Recession, with serious employment consequences for job losers, including very low rates of re-employment and difficulty finding full-time employment. The average reduction in weekly earnings for job losers making a full-time–full-time transition are relatively small, with a substantial minority reporting earning more on their new job than on the lost job. Most of the cost of job loss comes from difficulty finding new full-time employment.